Answer:
The sum of area of two smaller squares is equal to the area of bigger square
An equation using a, b, and c with exponents is [tex]c^2=a^2+b^2[/tex]
Step-by-step explanation:
Let a be the side of the smallest square , b be the side of other smaller square and c be the side of biggest square
Area of square with side a = [tex]Side^2 = a^2[/tex]
Area of square with side b = [tex]Side^2 = b^2[/tex]
Area of square with side c =[tex]Side^2 = c^2[/tex]
Refer the attached figure
In triangle ABC
[tex]\angle A = 90^{\circ}[/tex]
So, We can use Pythagoras theorem over here
AB = a = Base
AC = b = Perpendicular
BC = c = Hypotenuse
[tex]Hypotenuse^2=Perpendicular^2+Base^2\\c^2=a^2+b^2[/tex]
So, The sum of area of two smaller squares is equal to the area of bigger square
An equation using a, b, and c with exponents is [tex]c^2=a^2+b^2[/tex]